Ferroptosis as a potential therapeutic target for post-traumatic stress disorder - Zhang, Qian; Mao, Jin-Dong; Chen, Hui; Wang, Min; Wu, Yu-Mei; Wang, Chuan (Frontiers in Molecular Neuroscience, 2025)
The underlying mechanisms of post-traumatic stress disorder (PTSD) are still not fully understood, creating significant obstacles for developing effective therapeutic strategies. Recently, ferroptosis, an iron-dependent form of regulated cell death, has been shown to play a role in several psychiatric disorders, such as major depressive disorder (MDD), stress-induced anxiety, Alzheimer’s disease (AD), and Parkinson’s disease (PD). While direct evidence for the role of ferroptosis in PTSD is still limited, an increasing number of studies suggest that the pathological features of PTSD may trigger the ferroptosis cascade. Additionally, the typical hallmarks of ferroptosis, such as iron dysregulation, lipid peroxidation, and failure of antioxidant defense systems, may intersect with the pathogenesis of PTSD. Importantly, some treatments for PTSD, such as antioxidants and free radical scavengers, have been proven to inhibit ferroptosis, which further supports the case for ferroptosis as a potential pathogenic mechanism in PTSD. To thoroughly investigate the mechanistic links between ferroptosis and PTSD, we analyze the relevant literature on ferroptosis and PTSD in this review. Our aim is to elucidate the potential relationships between ferroptosis and PTSD, thereby providing novel insights for future research directions. Furthermore, we call for more experimental and clinical studies to explore this relationship further, with the ultimate goal of developing more effective therapeutic strategies for PTSD.